Magnetic Susceptibility as a Tool of Lithological Mapping: A Case Study from Malekhu-Damauli Area of Central Nepal, Lesser Himalaya - Acharya, Rajendra; Paudyal, Kabiraj (Nepal Journal of Science and Technology, 2016)
Magnetic susceptibility (MS) along different roads, foot-trails and river sections has been measured in rock outcrops. The measured major sections are Malekhu-Dhading road, Mugling-Jugedi road, Ghumaune-Damauli road, Mugling-Anbu Khaireni-Badinpur road, Shivapur- Gwaslung road, Malekhu Khola section, Trishuli and Seti river sections and other small tributaries near road sections. A pocket susceptibility meter (ZH Instruments SM30) was used to measure MS values of rocks which belong to the Nawakot Group, Bhimphedi Group and the Tanahun Group. For the values of MS in the study area, site mean MS (average of 10 to 15 readings at each outcrop) data gave the following variations: (i) a large range of average MS between (-0.0097 - 387) x 10-3 SI; (ii) lowest MS magnitudes (<0.1 x 10-3 SI ) for quartzite, limestone, dolomite, which are predominantly composed of diamagnetic minerals (e.g. quartz, calcite and dolomite); (iii) intermediate range of (0.1-1.0 x 10-3 SI) was found in most shales, slates, phyllites, sandstones and schists; and (iv) high values (>1.0 x 10-3 SI) for amphibolites, green-schists, metasandstones, and iron rich beds. The range of unique values of MS could be used for lithological mapping and hence the stratigraphic as well as structural interpretations. Nepal Journal of Science and Technology Vol. 16, No.1 (2015) pp.49-58